Correlation between perceived social support and quality of sleep and its effect on the academic performance of undergraduate medical students: A cross-sectional study - Khulbe, Pranita; Bartwal, Janki (Indian Journal of Community Health, 2024)
Background: Social support can be explained as the availability or existence of people who make us feel loved, cared for and valued, people on whom we can rely. Apart from physical health, social networking and interaction uplift mental health, well-being, and academic performance of individuals. Sleep has been associated with achievements in academic indicators of a person, as its deficit causes a lack of attention and concentration. Methods: A survey was designed to conduct cross-sectional study among the undergraduate medical students. The validated 12 item multidimensional scale of perceived social support and 19 self -rated questions of Pittsburgh sleep quality index was used for assessing the social support and sleep quality among the students and how it affected their academic performance. Data was collected in google forms and coded & cleaned and then exported for statistical analysis, to SPSS version 20. Results: Of the total 385 undergraduate medical students, majority were female respondent and from 2nd Professional. Most of the students scored between 60-69% in their university exam. Majority of the student has poor sleep quality. The academic performance has statistically significant association with perceived social support while age of the student was significantly associated with poor quality of sleep. A negative correlation was noted between perceived social support and sleep quality. Conclusion: This study has highlighted the negative impact of a lack of perceived social support on the sleep quality of medical students. Results also showed evidence of an overall poor quality of sleep in the medical students.